COVID-19 infection as a trigger for the manifestation of celiac disease in a 4-year-old child - Joanna Bińkowska; Anna Jarzumbek; Katarzyna Górowska-Kowolik; Jarosław Kwiecień (Termedia Publishing House, 2023)
The article presents the case of a girl who, after being infected with COVID-19, developed a seroconversion of anti-tissue transglutaminase antibodies as she developed symptoms from the gastrointestinal tract, which consequently allowed her to be diagnosed with celiac disease. In recent years, more and more articles describing possible autoimmune complications have been published after suffering from an infection caused by the SARS-CoV-2 virus. The aim of the work was to show how many diseases are potentially related to COVID-19 infection, pointing out that in the medical literature, the number of articles describing such cases in the paediatric population is still insufficient. We describe herein the case of a 4-year-old patient, who was diagnosed with celiac disease after suffering from COVID-19. We also aim to return attention to vigilantly observing any new symptoms that appear from various source organs after suffering an infection caused by the SARS-CoV-2 virus.